Pengaruh Model Cooperative Learning Tipe Jigsaw Berbantuan Media Eco-pop terhadap Kemampuan Berpikir Kritis Siswa SD - Anggi Harnum Lestari; Adit Rizki Sudrajat; Alya Awwaliyatin Kuswandi; Ani Saadah; Fadilah Nurfalah; Restika Wahyuni; Afridha Laily Alindra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Critical thinking skills are very necessary in the 21st century, several studies still show that students’ critical thinking skill in Indonesia are still low. This study aims to determine the effect of applying the Jigsaw type Cooperative Learning model assisted by Eco-pop media on the critical thinking skills of fifth-grade elementary school students. The research method used was a pre-experiment with a one group pretest-posttest design. The research subjects consisted of 20 fifth-grade elementary school students, namely 8 male students and 12 female students at an elementary school in Purwakarta. Data collection was carried out through test instruments in the form of pretest and posttest questions, each consisting of 10 essay questions that measured students’ critical thinking skills. Data analysis used parametric inferential statistics with the help of the SPSS application. The normality test results showed that the data were normally distributed, with a pretest significance value of 0.071 > 0.05 and a posttest significance value of 0.155 >0.05. The results of the Paired Sample T-Test showed a significance value of0.000 < 0.05, confirming a significant difference between critical thinking skills before and after treatment. Thus, it can be concluded that the Jigsaw Cooperative Learning model assisted by Eco-pop media has a significant effect in effectively improving the critical thinking skills of fifth-grade elementary school students and is recommended for use in the classroom learning process.